An Introduction to landfill cover and liner hazards - Guyer, J. Paul (California : The Clubhouse Press, 2021)
Introductory technical guidance for civil and environmental engineers, construction managers and landfill operators interested in safety hazardous presented by landfill covers and liners.
1. GENERAL -- 2. TECHNOLOGY DESCRIPTION -- 3. HAZARD ANALYSIS.
Keywords: LANDFILLS